2008
DOI: 10.1073/pnas.0709530105
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of the mycobacterial outer membrane: Cryo-electron tomography and vitreous sections reveal the lipid bilayer structure

Abstract: The cell walls of mycobacteria form an exceptional permeability barrier, and they are essential for virulence. They contain extractable lipids and long-chain mycolic acids that are covalently linked to peptidoglycan via an arabinogalactan network. The lipids were thought to form an asymmetrical bilayer of considerable thickness, but this could never be proven directly by microscopy or other means. Cryo-electron tomography of unperturbed or detergenttreated cells of Mycobacterium smegmatis embedded in vitreous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
480
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(504 citation statements)
references
References 42 publications
18
480
3
3
Order By: Relevance
“…Moreover, cell fractionation experiments and recent advances in electron microscopy have lent some credibility to the controversial concept of a Gram-positive 'periplasm' [4][5][6]. Cryoelectron microscopy has also provided evidence supporting the presence of an outer membrane permeability barrier in the mycolic acid-containing actinomycete bacteria Mycobacterium smegmatis, Mycobacterium bovis and Corynebacterium glutamicum [7,8]. In addition, since the last review of Gram-positive lipoproteins 13 years ago [3] our understanding of the diverse functions of these proteins has been greatly advanced by the availability of whole genome sequence data.…”
Section: Bacterial Lipoproteinsmentioning
confidence: 96%
“…Moreover, cell fractionation experiments and recent advances in electron microscopy have lent some credibility to the controversial concept of a Gram-positive 'periplasm' [4][5][6]. Cryoelectron microscopy has also provided evidence supporting the presence of an outer membrane permeability barrier in the mycolic acid-containing actinomycete bacteria Mycobacterium smegmatis, Mycobacterium bovis and Corynebacterium glutamicum [7,8]. In addition, since the last review of Gram-positive lipoproteins 13 years ago [3] our understanding of the diverse functions of these proteins has been greatly advanced by the availability of whole genome sequence data.…”
Section: Bacterial Lipoproteinsmentioning
confidence: 96%
“…Although Mycobacteria belong to the gram1 bacteria, which are generally assumed to have no OM recent studies showed the existence of such a membrane for some members of the genera (15). The mycobacterial OM is described to comprise a bilayer which is even thicker than the IM but of different structure than that of gram2 bacteria.…”
Section: Outer Membranes (Om)mentioning
confidence: 99%
“…Nevertheless, mycolic acids are located in the inner leaflet of the OM causing a highly ordered structure (16). The addition of detergents like Tween 60 may initiate alteration of fluidity of the mycolic acid layer (16), which in consequence may turn to be leaky to amphiphilic molecules (15).…”
Section: Outer Membranes (Om)mentioning
confidence: 99%
“…In spite of a good knowledge of the chemical composition of the mycobacterial surface, not much is known about its organization and physiology (Barry, 2001). The recent demonstration of the presence of an outer membrane will surely boost research in this field (Hoffmann et al, 2008;Zuber et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a good knowledge of the chemical composition of the mycobacterial surface, not much is known about its organization and physiology (Barry, 2001). The recent demonstration of the presence of an outer membrane will surely boost research in this field (Hoffmann et al, 2008;Zuber et al, 2008).One strategy to study bacterial surface physiology is to characterize the variation of the bacterial transcriptional profile in response to exposure to compounds able to perturb surface homeostasis. This approach has been successfully used to study the global transcriptional response of Bacillus subtilis and Staphylococcus aureus in response to several inhibitors of peptidoglycan biosynthesis (Cao et al, 2002;Mascher et al, 2003;Utaida et al, 2003), and in M. tuberculosis to study the transcriptional response to the Abbreviations: HCL, hierarchical clustering; SAM, significance analysis of microarrays.…”
mentioning
confidence: 99%